Perceived influence of opposition political campaign materials on voters - Syed Abdullah Idid, Syed Arabi; Souket, Rizwanah (EDP Sciences, 2017)
This article focuses on how political attitudes of voters are shaped and affected during election campaigns. The study is constructed on the third person effect paradigm that posits that negative messages will have a greater impact not on ‘me’ or ‘you’ but on ‘them’. Concurrently, perceived positive messages will have a greater influence on themselves compared to others, often referred to as the first-person effect or reverse third person effect (Duck, Terry & Hogg, 1995; Perloff 1999). The present study was undertaken to understand how political communication messages can have a positive effect on own party supporters while the same message can be perceived to be biased and partisan to opposing party supporters. The current study is grounded on the research done by Idid & Souket (2014) that investigated the effects of Malaysia’s largest political party, Barisan Nasional (BN) political communication literature on two Malaysian voter groups (BN voters and opposition voters), one of which regarded the message as partisan and the other as congenial. The present study attempts to investigate the effects of each of the opposition party political communication literature on two Malaysian voter groups (BN party supporters and the particular opposition party supporter).